How the Three Generations of Administrators Advanced an HEI, What Crises They Encountered, and How They Handled Them: A Qualitative Case Study - Cacayan, Richard (International Journal of Sustainability and Advanced Integrated Research, 2026)
This qualitative case study examined how three generations of administrators advanced a faith-based higher education institution, the crises they encountered during their respective terms, and the strategies they employed to manage these challenges. Grounded in transformational leadership theory, the study involved three former administrators selected through purposive sampling. Data were gathered through semi-structured, in-depth interviews using open-ended and probing questions. The interviews were audio-recorded, transcribed verbatim, and supported through triangulation involving employee interviews, institutional records, yearbooks, articles, and the researcher’s observations. Manual thematic analysis was used to identify recurring patterns and themes. The findings showed that the administrators advanced the institution through quality assurance and accreditation, faculty and staff development, spiritual development, collaborative governance, program and infrastructure development, and financial management. The major crises involved financial management difficulties, leadership and governance conflicts, operational inefficiencies, and concerns regarding staff qualifications. These challenges were addressed through teamwork and collaboration, clear communication and informed decision-making, structured planning and implementation, and institutional, personal, and spiritual support systems. The study concludes that collaborative governance, strategic planning, transparent communication, and stakeholder participation are essential to institutional stability, resilience, and continued advancement. It recommends longitudinal studies on the development and long-term effects of leadership practices and further investigation of how leadership styles respond to different generational groups. The study supports SDG 4 on Quality Education, SDG 9 on Industry, Innovation and Infrastructure, SDG 16 on Peace, Justice and Strong Institutions, and SDG 17 on Partnerships for the Goals. It contributes to educational, institutional, governance, technological, human resource, and cultural sustainability by informing leadership development, succession planning, crisis management, and institutional continuity.